PERFORMANCE BETWEEN THE MEDAN CITY GOVERNMENT AND THE DELI SERDANG REGENCY GOVERNMENT - Bajongga Juan Nadi Togatorop; Hendry Glenn Yose Sinambela; Rajwa Khairi; Iskandar Muda; Andy Mulia (JIAR : Journal Of International Accounting Research, 2025)
This study aims to determine and compare the performance of Regional Revenue and Expenditure Budget (APBD) management in 2025. The method used is quantitative with a comparative descriptive approach. The analysis was conducted using regional financial ratios, including independence, effectiveness, efficiency, harmony, and growth ratios. The data source is secondary data in the form of APBD realization reports. The results show that Medan City has a higher level of financial independence compared to Deli Serdang Regency. However, its financial management is not yet optimal due to low effectiveness and the dominance of operational expenditures in the budget. Deli Serdang Regency has a lower level of financial independence but demonstrates better performance in terms of effectiveness and efficiency. Its expenditure structure is more balanced, and revenue growth tends to increase. It can be concluded that regions with high revenue do not necessarily have good financial management. Therefore, Medan City needs to improve its budget management, while Deli Serdang Regency needs to increase its level of financial independence.